Comparative Diagnostic Accuracy of LF-LAM TB Antigen and Xpert MTB/RIF in Pulmonary Tuberculosis among Underweight Patients - Eksa, Dwi Robbiardy; Hendarto, Gatot Sudiro; Sinaga, Fransisca TY; Dilangga, Pad; Herdato, M. Junus Didiek; Infianto, Andreas; Ekawati, Diyan; Gozali, Achmad; Ajipurnomo, Adhari (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2025)
Background: In 2023, the global incidence of tuberculosis (TB) reached 8.2 million cases. It is the highest on record due to delayed diagnoses and a rising number of TB patients. Tuberculosis is more prevalent among patients with compromised immune systems, including those with HIV and malnutrition (BMI <18.5 kg/m2), who exhibit increased vulnerability to infection. The challenge of sputum expulsion impedes diagnosis, requiring a rapid, cost-effective early-detection technique. The lateral flow lipoarabinomannan TB antigen (LF-LAM TB-Ag) assay provides an alternate method for identifying lipoarabinomannan in urine, a constituent of the Mycobacterium tuberculosis cell wall. This study assessed the effectiveness of the LF-LAM TB-Ag assay compared with the Xpert MTB/RIF assay for TB diagnosis. Methods: A comparative cross-sectional study was conducted at Abdul Moeloek Hospital, Lampung Province, from January 2023 to June 2024. A total of 52 suspected pulmonary TB patients with HIV-negative status and underweight BMI were evaluated using both the LF-LAM TB-Ag and Xpert MTB/RIF assays. Results: Chi-square tests were used to compare the performance of LF-LAM TB-Ag with Xpert MTB/RIF. The LF-LAM TB-Ag test had a sensitivity of 79.59% and a specificity of 100% (P=0.002). Conclusion: This study underscores the necessity for early detection of pulmonary TB in underweight individuals. The integration of LF-LAM TB-Ag with Xpert MTB/RIF improves detection, especially in high-risk populations, enabling prompt treatment and enhanced disease management.